Des modèles de formation professionnelle d'origine étrangère à l'épreuve des spécificités sociétales marocaines - Mohamed Jallal Eladnani; Éric Verdier (Les éditions de la Maison des sciences de l'Homme, 2008)
The present system of vocational training in Morocco is an assembly of models and categories of policy making largely inspired from different countries of the OECD. If the choice of the scholar vocational training has its origin in the common history of both countries, the introduction of other models (dual and vocational training inspired from Germany and Belgium) constructs a composite configuration that results from a socio-political process. These two models are based on an other conception of the regulation of the vocational training-employment relationship, in term of " occupational market " that implies that the Moroccan enterprises should participate actively in the production of skills and qualifications. This institutional setting is structured by the rules of the school-enterprise alternating, what distinguishes this formula of the model of the traditional apprenticeship. The application of the Canadian Competency-Based-Education is linked to an other design of the coordination between training centers and workshops.In Morocco the handcraft is anchored in a multi-centuries tradition; so it is a relevant way for analyzing this complex configuration. This choice is justified by the fact it allows to confront the " modern " devices of vocational training to the traditional on the job training. So it is possible to reveal the result of co-existence between foreign models and traditional ways to produce the skills.